Curcumin Inhibits Hepatocellular Carcinoma via Regulating miR-21/TIMP3 Axis. (17th July 2020) - Li, Jingtao; Wei, Hailiang; Liu, Yonggang; Li, Qian; Guo, Hui; Guo, Yingjun; Chang, Zhanjie
Abstract : Background/Aim . Curcumin exhibits anticancer effects against various types of cancer including hepatocellular carcinoma (HCC). miR-21 has been reported to be involved in the malignant biological properties of HCC. However, whether miR-21 plays a role in curcumin-mediated treatment of HCC is unknown. The purpose of this study was to identify the potential functions and mechanisms of miR-21 in curcumin-mediated treatment of HCC. Methods . The anticancer effects of curcumin were assessed in vivo and in vitro. The underlying mechanism of miR-21 in curcumin-mediated treatment of HCC was assessed by quantitative real-time PCR (RT-qPCR), western blot, and Dual-Luciferase Reporter assays. Results . The present study revealed that curcumin suppressed HCC growth in vivo and inhibited HCC cell proliferation and induced cell apoptosis in a dose-dependent manner in vitro. Meanwhile, the curcumin treatment can downregulate miR-21 expression, upregulate TIMP3 expression, and inhibit the TGF- β 1/smad3 signaling pathway. miR-21 inhibition enhanced the effect of curcumin on cell proliferation inhibition, apoptosis, and TGF- β 1/smad3 signaling pathway inhibition in HepG2 and HCCLM3 cells. It demonstrated that TIMP3 was a direct target gene of miR-21. Interestingly, the effect of miR-21 inhibition on cell proliferation, apoptosis, and TGF- β 1/smad3 signaling pathway in HepG2 and HCCLM3 cells exposed to curcumin was attenuated by TIMP3 silencing. Conclusion . Taken together, the present study suggests that miR-21 is involved in the anticancer activities of curcumin through targeting TIMP3, and the mechanism possibly refers to the inhibition of TGF- β 1/smad3 signaling pathway.